2016
DOI: 10.1007/s11274-016-2149-6
|View full text |Cite
|
Sign up to set email alerts
|

Communities of endophytic microorganisms in different developmental stages from a local variety as well as transgenic and conventional isogenic hybrids of maize

Abstract: The diversity of endophytic microorganisms may change due to the genotype of the host plant and its phenological stage. In this study we evaluated the effect of phenological stage, transgenes and genetic composition of maize on endophytic bacterial and fungal communities. The maize populations were composed of a local variety named Rosado (RS) and three isogenic hybrids. One isogenic hybrid was not genetically modified (NGM). Another hybrid (Hx) contained the transgenes cry1F and pat (T1507 event), which provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…transgenesis and genome editing), and experience shows that interactions with the environment known from conventional plant breeding cannot simply be extrapolated to GE plants. For example, da Silva et al [82] and Wallace et al [83] show differences in the associated microbiomes of transgenic plants are not only influenced by the environment but to some extent also impacted by plant genetics. Therefore, ERA of GE organisms should include potential (intended and unintended) changes of these signalling pathways since they can substantially disturb or even disrupt the functions of the ecosystems.…”
Section: Other Effects and Interactions Of Relevance For Risk Assessmmentioning
confidence: 99%
“…transgenesis and genome editing), and experience shows that interactions with the environment known from conventional plant breeding cannot simply be extrapolated to GE plants. For example, da Silva et al [82] and Wallace et al [83] show differences in the associated microbiomes of transgenic plants are not only influenced by the environment but to some extent also impacted by plant genetics. Therefore, ERA of GE organisms should include potential (intended and unintended) changes of these signalling pathways since they can substantially disturb or even disrupt the functions of the ecosystems.…”
Section: Other Effects and Interactions Of Relevance For Risk Assessmmentioning
confidence: 99%
“…In addition, host genotypes might influence the microbiome that engages in symbiosis with plants. Silva et al (2014, 2016) found that the decisive factor of changes in the endogenous bacterial, fungal, and archaeal communities of maize was the genotype of the maize plants. Meanwhile, other studies showed that endophytic bacteria from maize, rice, and potato were more susceptible to the different stages of plant development and pathogen exposure (Rasche et al, 2006; Janpen et al, 2009; Inceoğlu et al, 2010; Rangjaroen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, life forms can only be assessed in combination with their environment: for example, the well-established concept of the 'holobiont' (see for example Richardson 2017) shows that multicellular organisms such as plants, insects or mammals can hardly be separated from their associated microbiome. The organism and its associated microbiome interact very closely: it is known that the microbiome can extensively impact the biological characteristics and health status of humans, plants and animals (see for example Lynch and Pedersen 2016;da Silva et al 2016).…”
Section: What Is the Entity That Has To Be Assessed?mentioning
confidence: 99%